ANALISIS MOTIVASI BELAJAR BAHASA INDONESIA DI SEKOLAH DENGAN KURIKULUM ASING: SEBUAH STUDI KASUS SEKOLAH XYZ [AN ANALYSIS OF INDONESIAN LANGUAGE LEARNING MOTIVATION USING FOREIGN CURRICULUM: A CASE STUDY AT SCHOOL XYZ] - Sri Utami; Fransisco Budi Hardiman (Universitas Pelita Harapan, 2021)
The low learning motivation in students studying Indonesian language is often encountered in a school using international curriculum. This was also found at XYZ school, where the issue encountered is of a particular one. The Indonesian language subject has led students to experience stress, moving out to language B course, and even moving into a new school. This is a case-study research involving 3 respondents and 7 participants. This case-study research was conducted during the Covid 19 pandemic; thus, all data collection was done online. The techniques used to collect data include open questionnaires, in-depth interviews, observations, and document reviews. Data validity was tested through data triangulation. The results showed that internal factors, namely student’s perspective on Indonesian language and external factors which are family background, curriculum policies and teacher quality greatly affect to students’ motivation. The role of parents, teachers, as well as curriculum policies are crucial to increase the students’ learning motivation in studying Indonesian language.BAHASA INDONESIA ABSTRACT: Rendahnya motivasi belajar bahasa Indonesia siswa di sekolah dengan kurikulum asing merupakan masalah yang sering ditemui. Hal tersebut juga ditemui di sekolah XYZ, namun permasalahan yang ditemui di sekolah XYZ sangat khusus, karena pelajaran bahasa Indonesia mengakibatkan siswa mengalami stres, pindah ke kelas BI B, dan bahkan pindah sekolah. Penilitian ini merupakan penelitian studi kasus yang melibatkan 3 responden dan 7 partisipan. Penelitian studi kasus ini dilakukan dalam situasi pandemi Covid 19 dan semua pengumpulan data dilakukan secara daring. Teknik pengumpulan data menggunakan kuesioner terbuka, wawancara mendalam, pengamatan, dan kajian dokumen. Keabsahan data diuji melalui triangulasi data. Hasil penelitian menunjukkan bahwa faktor internal, yaitu perspektif siswa tentang pembelajaran bahasa Indonesia dan faktor eksternal yaitu latar belakang keluarga, kebijakan kurikulum, dan cara mengajar guru sangat mempengaruhi motivasi belajar bahasa Indonesia siswa. Peranan orang tua, guru, dan kebijakan kurikulum sangat penting untuk meningkatkan motivasi belajar bahasa Indonesia pada siswa.